2021
DOI: 10.1021/jacs.0c10465
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Porous Melanin

Abstract: Commonly known as a skin pigment, melanin has a vital role in UV radiation protection, primarily acting as a radical scavenger. However, a lesser known natural property of melanin, observed in some melanized organisms, is its capacity to adsorb toxins, including metals and organic molecules. Inspired by this, we set out to generate a synthetic porous melanin that would pave the way to enhancing the natural adsorbent properties of melanin and melanin-like materials. Here, we developed a method for the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 80 publications
0
37
0
Order By: Relevance
“…This is in agreement with the findings of Rahmani Eliato et al 20 who reported that the size of horsehair melanin pores is in the range of 3–5 nm. Such pore sizes and large specific surface area make date fruit melanin a suitable candidate for various applications such as a natural toxins absorber 21 .
Figure 4 Date fruit melanin particle characteristics, ( a ) Scanning electron microscopic (SEM) Images of melanin particles at different magnification, ( b ) Sorption isotherm, ( c ) Relative Barret-Joyner Halender (BJH) pore size calculated from the sorption isotherm, ( d ) X-ray diffraction (XRD) profile showing the amorphous nature of the melanin.
…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the findings of Rahmani Eliato et al 20 who reported that the size of horsehair melanin pores is in the range of 3–5 nm. Such pore sizes and large specific surface area make date fruit melanin a suitable candidate for various applications such as a natural toxins absorber 21 .
Figure 4 Date fruit melanin particle characteristics, ( a ) Scanning electron microscopic (SEM) Images of melanin particles at different magnification, ( b ) Sorption isotherm, ( c ) Relative Barret-Joyner Halender (BJH) pore size calculated from the sorption isotherm, ( d ) X-ray diffraction (XRD) profile showing the amorphous nature of the melanin.
…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to these methods, we used polydopamine (PDA) to protect pristine GNR probe from the shape deformation. PDA coatings are robust, biocompatible, and surface functionalization [28,29]. We thus hypothesized that PDA is a pragmatic choice as a GNR shape-preserving coating for theranostic applications.…”
Section: Introductionmentioning
confidence: 99%
“…While the PBDT nanoparticles are primarily stabilized by p-p interactions, the formation of PDA is dominated by robust covalent interactions. [43,44] Therefore, we hypothesized that the supramolecular PBDT nanoparticles would be removed during the solvent treatment to produce uniform PDA nanocapsules. [45] This is corroborated by incubating the core-shell nanoparticles in dimethyl sulfoxide (DMSO) for 15 min: SEM and atomic force microscopy (AFM) demonstrated the transformation of core-shell nanoparticles into crumpled nanocapsules via DMSO (Figure 3 b-e and S10,11).…”
Section: Methodsmentioning
confidence: 99%